Radicals in English education, 1960-1980: A critical study - Wright, Nigel Philip (1988)
This is an interdisciplinary critical review of the radical movement in English education (schools) in the 1960s and 1970s. The term 'radical’ is defined and the contributing historical currents are analysed. The distinguishing features of this radicalism are identified. There is a descriptive history of 19 radical teachers' groups, of the school students movement and of the other groups which campaigned for radical changes in education. The ideas and strategies of these groups are examined and discussed. As examples of radical practice, the 14 free schools which were established in the 1970s are described. The phenomenon of free schooling is investigated under six headings: philosophy; the free school and the community: structures; the place of free schools in society; libertarian non-intervention; and the strategy of free schooling. Twelve 'radical dilemmas' are identified - issues on which the radicals were unable to reach agreement and which rendered the radical movement a multi-dimensional tendency rather than a unified political movement. The ideas put forward by the radicals are critically examined in two case studies: one a study of the experience of White Lion Street Free School; the other a study of radical theories of learning. In each case it is suggested that there are flaws in radical thinking which point to a need for more rigorous theoretical work. Certain themes which were under-developed by radicals are identified. The significance of the radical movement is assessed, and proposals are made for further research. An appendix lists all the criticisms made of schooling by the radicals in this period. The bibliography includes a comprehensive list of all the radical literature published in this period